Assessment of the effect of electromagnetic radiation from cell phones using the Daphnia magna test object (ҚазҰУ хабаршысы. Экология сериясы, 2022)
Currently, the problem of electromagnetic safety of the population has acquired social significance and is an urgent issue for the modern development of the Republic of Kazakhstan, as well as for other countries of the world. Environmental exposure to radiofrequency electromagnetic fields from mobile phones has rapidly increased in the last two decades and this trend is expected to continue. Modern technologies have become a source of electromagnetic pollution generated electromagnetic fields. Due to the increase in technogenic processes and their influence on the Earth’s electromagnetic field, the topic of the influence of electromagnetic radiation on living organisms has been increasingly studied. All sources of electromagnetic fields, as a rule, are a source of complex electromagnetic radiation that affects plants, animals, insects and soil flora in the zone of influence of electromagnetic fields. The effect of the electromagnetic fields emitted from cell phones on living organisms and human health have become one of the most important topics for research because cell phones are widely used all over the world. In many countries, cellular communication occupies a special place among anthropogenic sources of electromagnetic radiation. A cell phone is a small-sized transceiver operating in the 900/1800 MHz range, which refers to damaging environmental factors. The influence of electromagnetic radiation of cell phones on the abundance of Daphnia magna was investigated. Radiation effects are clearly evident in the toxicology study with Samsung Galaxy J7 and Vivo V 20 cell phones. During the experiment, the radiation of these models of cell phones was established, and the abundance under the influence of Vivo V 20 was higher than under the influence of Samsung Galaxy J7, but lower than in the control group.Key words: electromagnetic radiation, electromagnetic fields, cell phone, Daphnia culture, amount, hydrobionts.